Social Factors and Coping Models of Women as The Violence Victims In Ponorogo District - Ridho Rokamah; Rif'ah Roihanah (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2019)
This study examines the social factors and coping models of women as victims of domestic violence after divorce. This research used the qualitative approach while the data collection techniques are included an interview, observation, and documentation. This study's conclusions are (1) social factors, from an education point of view, they consist of the lowest education, namely junior high school and the highest in college. From their social status consisting of low, medium, and high social status, and from environmental factors, it can be concluded that respondents come from various social environments. Other factors that trigger the violence occur to women such as age, economy, independence, career women, etc. (2) The coping model of women as the victims of violence in facing post-divorce stressors in Ponorogo Regency is divided into two; namely, the problem focuses coping and emotional focused coping.Penelitian ini mengkaji bagaimana faktor sosial dan model coping perempuan korban kekerasan dalam rumah tangga pasca perceraian. Pendekatan penelitian yang digunakan dalam penelitian ini adalah pendekatan kualitatif. Sedangkan teknik pengumpulan datanya meliputi wawancara, observasi dan dokumentasi. Kesimpulan dari penelitian ini adalah: 1) faktor sosial apabila dilihat dari pendidikan, mereka terdiri dari pendidikan terendah yaitu SMP dan tertinggi perguruan tinggi, dilihat dari status sosial mereka terdiri atas status sosial rendah, sedang, dan tinggi, dan jika dilihat dari faktor lingkungan, sehingga bisa disimpulkan responden berasal dari lingkungan sosial yang beragam, dan ada faktor lain yang menyebabkan kekerasan terjadi terhadap perempuan seperti masalah usia, ekonomi, kemandirian isteri, pekerjaan isteri, dan lain-lain. Dan 2) model coping perempuan korban kekerasan dalam menghadapi stressor pasca perceraian di Kabupaten Ponorogo terbagi menjadi dua yaitu; Problem Focus Coping dan Emosional Focused coping.